Simulated kalman filter with modified measurement, substitution mutation and hamming distance calculation for solving traveling salesman problem - Suhazri Amrin, Rahmad; Zuwairie, Ibrahim; Zulkifli, Md. Yusof (Springer International Publishing, 2022)
Background - Combinatorial optimization is a problem that consists of finding the optimum combination of each component from a finite set of objects. Most metaheuristic algorithms are designed for continuous optimization problem. Modification or enhancement is needed for continuous algorithm to solve combinatorial optimization problem.